2017
DOI: 10.1080/10236198.2017.1340468
|View full text |Cite
|
Sign up to set email alerts
|

On chaotic behaviour of the p-adic generalized Ising mapping and its application

Abstract: Abstract. In the present paper, by conducting research on the dynamics of the p-adic generalized Ising mapping corresponding to renormalization group associated with the p-adic Ising-Vannemenus model on a Cayley tree, we have determined the existence of the fixed points of a given function. Simultaneously, the attractors of the dynamical system have been found. We have come to a conclusion that the considered mapping is topologically conjugate to the symbolic shift which implies its chaoticity and as an applic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…We stress that the Potts–Ising mapping is a particular case of the Potts–Bethe mapping, which can be obtained from (1.1) by putting . Recently, in [30, 34] under some condition, a Julia set of the Potts–Ising mapping was described, and it was shown that restricted to its Julia set, the Potts–Ising mapping is conjugate to a full shift. Therefore, it is natural to consider the Potts–Bethe mapping for with and .…”
Section: Introductionmentioning
confidence: 99%
“…We stress that the Potts–Ising mapping is a particular case of the Potts–Bethe mapping, which can be obtained from (1.1) by putting . Recently, in [30, 34] under some condition, a Julia set of the Potts–Ising mapping was described, and it was shown that restricted to its Julia set, the Potts–Ising mapping is conjugate to a full shift. Therefore, it is natural to consider the Potts–Bethe mapping for with and .…”
Section: Introductionmentioning
confidence: 99%
“…We stress that the Potts-Ising mapping is a particular case of the Potts-Bethe mapping, which can be obtained from (1.1) by putting q = 2. Recently, in [17,21] under some condition, a Julia set of the Potts-Ising mapping have been described, and it was shown this mapping is conjugate to the full shift. Therefore, it is natural to consider the the Potts-Bethe mapping for q ≥ 3 with |q| p < 1 and k ≥ 2.…”
Section: Introductionmentioning
confidence: 99%